The Impact Of Internet Technologies On Tourism Development - Sharofutdinov Iskandar Baxodirovich (Open Academia, 2025)
Today, before going to the country, every tourist is curious about the peculiarities of that country through the Internet. In today's language, he organizes an online trip to the country first of all. This article talks about the role and importance of Internet resources in the development of tourism today
Keywords: Mobile internet; tourist sites; business card sites